2021
DOI: 10.1021/acsomega.1c00374
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Polymer/Graphene Oxide Composite as a Fluid Loss Agent for Water-Based Drilling Fluids

Abstract: The wellbore instability caused by the penetration of drilling fluids into the formation is a vital problem in the drilling process. In this study, we synthesized a polymer/graphene oxide composite (PAAN-G) as a fluid loss additive in water-based drilling fluids. The three monomers (acrylamide (AM), 2-acrylamide-2-methyl-1-propane sulfonic acid (AMPS), N -vinylpyrrolidone (NVP)) and graphene oxide (GO) were copolymerized using aqueous free radical polymerization. The composition, micromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 52 publications
0
38
0
Order By: Relevance
“…The fluid losses feature was attributed to the fact that addition of PGON promoted a major particle density and thinner and denser filter cake. 72 Similarly, Kosynkin et al (2012) also showed the effect of the different graphene layer diameter on the fluid losses. In fact, they reported improved filtration properties for a mixture of large flakes graphene oxide nanoparticles (LFGNs) and graphene oxide powder nanoparticles (PGOs) formulation.…”
Section: Factors Affecting Wbdf Formulation Using 2d Nanomaterials As...mentioning
confidence: 94%
“…The fluid losses feature was attributed to the fact that addition of PGON promoted a major particle density and thinner and denser filter cake. 72 Similarly, Kosynkin et al (2012) also showed the effect of the different graphene layer diameter on the fluid losses. In fact, they reported improved filtration properties for a mixture of large flakes graphene oxide nanoparticles (LFGNs) and graphene oxide powder nanoparticles (PGOs) formulation.…”
Section: Factors Affecting Wbdf Formulation Using 2d Nanomaterials As...mentioning
confidence: 94%
“…However, in this study a constant ratio has been used to analyze the effect of GO-PAM on the drilling fluid compared to using GO. 46,53 Fourier transform infrared spectrometry (FTIR) was implemented to analyze the composition and structures of the GO-PAM nanocomposite. Dynamic light scattering and scanning electron microscopy were also performed for analyzing the size distribution and surface morphologies in this study.…”
Section: ■ Experimental Studymentioning
confidence: 99%
“…It should be noted that the ratio of water/monomer or water/GO could be variable to produce a nanocomposite or polymer with different properties. However, in this study a constant ratio has been used to analyze the effect of GO-PAM on the drilling fluid compared to using GO. , …”
Section: Experimental Studymentioning
confidence: 99%
See 1 more Smart Citation
“…One of our previous studies introduced graphene oxide into the polymer, and its calcium resistance reached 25 wt %. 39 However, at higher concentrations of calcium contamination, the polymer could not continue to maintain fluid loss reduction capacity. Thus, to reduce the fluid loss of WBDFs in the salt layer containing high concentrations of Na + and Ca 2+ , it is also necessary to study the fluid loss agent with the ability to resist high salt/calcium.…”
Section: Introductionmentioning
confidence: 99%